Ranger le monde. "Féerie générale" d’Emmanuelle Pireyre - Lis, Jerzy (Wydawnictwo Naukowe UAM, 2013)
To describe the world and to put some order into our contemporaneity, Emmanuelle Pireyre gathered in his novel titled "Féérie générale "(2012) numerous examples of situations that are symptomatic of the reality of the last years. Written in a way that highlights all the nuances of everyday life and interspersed either with the narrator’s opinions on modern society, or with dreams, extracts of electronic notices, anecdotes, or even with the presentation of a collection of kisses, the stories summarize the discontinuous and complex world. Denouncing the aberrations of society, the narrator confronts the clichés and the ideas people do not have time to think about, suggesting that we see in this world only the beautiful things, love and happiness, feelings considered futile by the thinkers and the creators. In this collection of magic things, Pireyre invites at the same time the readers to distance themselves from the disorder of the world and to live on a kind of islands of happiness.
Tidying up the world. "Féerie générale" by Emmanuelle Pireyre
Keywords: contemporary novel; everyday; enchantment; happiness; disorder; electronic media